Are ambulatory blood pressure parameters associated more with central adiposity than with total adiposity? Results of the ELSA-Brasil study - Souza, Ângela Maria Natal de; Griep, Rosane Harter; Hermsdorff, Helen Hermana Miranda; Fonseca, Maria de Jesus Mendes da; Juvanhol, Leidjaira Lopes (Frontiers in Cardiovascular Medicine, 2023)
Brackground: Worldwide obesity has a high prevalence, as well as carries a high risk of several chronic diseases, including hypertension. Studies of the association between obesity and ambulatory blood pressure (BP) are scarce and most use only body mass index (BMI) as indicator of adiposity. Thus, we aimed to examine for associations between total and central adiposity and ambulatory BP parameters (BP means and variability, nocturnal dipping and morning surge) among participants in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Methods: This crosssectional study (2012-2014) used a subsample of participants (n=812) of ELSA-Brasil who underwent 24-hour ambulatory BP monitoring to assess systolic and diastolic BP (SBP and DBP, respectively) over 24-hour periods and sub-periods. Indicators for total adiposity were BMI and body fat (BF) and, for central adiposity, waist circumference (WC) and waist-to-height ratio (WHR). Associations were tested using crude and adjusted gamma and logistic regression. Results: Overweight (BMI) and abdominal obesity (WC and WHR) associated positively with mean 24-hour (Coef= 2.71, 3.09 and 4.00, respectively), waking (Coef= 2.87, 3.26 and 4.16, respectively), and sleeping (Coef= 2.30, 2.74 and 3.50, respectively) SBP; mean DBP associated with high WHR in these three periods (Coef= 2.00, 2.10 and 1.68, respectively) and with WC in the waking period (Coef= 1.44). Overweight and abdominal obesity (WC and WHR) were positively associated with SBP variability over 24 hours (Coef= 0.53, 0.45 and 0.49, respectively) and in sleep (Coef= 0.80, 0.74 and 0.59, respectively), and with DBP variability in 24 hours (Coef= 0.64, 0.73 and 0.58, respectively), wakefulness (Coef= 0.50, 0.52 and 0.52, respectively) and sleep (Coef= 0.53, 0.45 and 0.49); excess BF associated positively with DBP variability over 24 hours (Coef= 0.43) and in wakefulness (Coef= 0.38). Lastly, high WHR and excess BF were associated with higher odds of extreme dipping (OR= 1.03 for both), while high WC and WHR associated with higher odds of exacerbated diastolic morning surge (OR= 3.18 and 3.66, respectively). Conclusion: Indicators of adiposity were associated with the BP means and variability, nocturnal dipping and morning surge, with more substantial results for indicators of central adiposity that the others.